Researchers of Culture Confronted with the “Treasures of Culinary Heritage” in Upper Silesia as Described in the Most Recent Cookbooks - Smolińska, Teresa (Łódzkie Studia Etnograficzne, 2015)
Considering that in the last few years culinary matters have become a fashionable topic, the author is making a preliminary attempt at assessing many myths and authoritative opinions related to it. With respect to this aim, she has reviewed utilitarian literature, to which culinary handbooks certainly belong ("Concerning the studies of comestibles in culture"). In this context, she has singled out cookery books pertaining to only one region, Upper Silesia. This region has a complicated history, being an ethnic borderland, where after the 2nd World War, the local population of Silesians acquired new neighbours: repatriates from the Eastern Borderlands annexed by the Soviet Union, settlers from central and southern Poland, as well as former emigrants coming back from the West ("The treasures of culinary heritage’ in cookery books from Upper Silesia"). The author discusses several Silesian cookery books which focus only on the specificity of traditional Silesian cuisine, the Silesians’ curious conservatism and attachment to their regional tastes and culinary customs, their preference for some products and dislike of other ones. From the well-provided shelf of Silesian cookery books, she has singled out two recently published, unusual culinary handbooks by the Rev. Father Prof. Andrzej Hanich (Opolszczyzna w wielu smakach. Skarby dziedzictwa kulinarnego. 2200 wypróbowanych i polecanych przepisów na przysmaki kuchni domowej, Opole 2012; Smaki polskie i opolskie. Skarby dziedzictwa kulinarnego. 2500 wypróbowanych i polecanych przepisów na przysmaki kuchni domowej, Opole 2014), which have become a culinary bestseller in Upper Silesia. The author perceives these books as an interesting and unusual example of a monothematic "collective lecture" pertaining to the multi-cultural character of Opole Silesia, the noticeable foreign influences and the globalisation of culinaries. In her opinion, these books constitute a very rich set of materials pertaining to the present-day culture of consumption in Poland, with a discernible emphasis on Opole Silesia.